THE PROFILE STABILITY OF THE ARTIFICIAL SAND BEACH NOURISHMENT - Setyandito, Oki; Nizam, Nizam; Triatmaja, Radianta; Yuwono, Nur (International Journals of Engineering & Sciences, 2012)
A thorough study concerning the artificial sandy beach slope stability is studiedin this paper. The performance analysis of the cross shore profile was using experimental approaches. A 2 (Two) - dimensional physical model was set up in the laboratory wave flume. The initial slopes (n) of the artificial sand beach model are n =1:6. This study result also compared with some theories established from previous research. The results indicate that the sandy beach slopes are adjusted due to wave attack to form either steeper or flatter stable slopes. The range of stable slopes (nf1) are 3 ≤n ≤ 12. It was observed that the sand particles at the lower part of the slope are transported upward and deposited at a higher part of the slope and vice versa. Experimental result showed the stability of beach profile with the utilization of bar as well as berm. The result also showed significant corelation between stabilizing slope (tan α) and wave steepness (H0/L0).